2020
DOI: 10.1590/1678-4685-gmb-2018-0160
|View full text |Cite
|
Sign up to set email alerts
|

Targeting STAT-3 signaling pathway in cancer for development of novel drugs: Advancements and challenges

Abstract: Signal transducers and activators of transcription 3 (STAT-3) is a transcription factor that regulates the gene expression of several target genes. These factors are activated by the binding of cytokines and growth factors with STAT-3 specific receptors on cell membrane. Few years ago, STAT-3 was considered an acute phase response element having several cellular functions such as inflammation, cell survival, invasion, metastasis and proliferation, genetic alteration, and angiogenesis. STAT-3 is activated by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 209 publications
(223 reference statements)
0
17
0
Order By: Relevance
“…In Gp 130 Y757F mutant macrophages, the induction of transcriptional repressor can inhibit inflammatory gene responses in STAT-3 signaling by IL-6 50 . Therefore, efficient anti-inflammatory feedback can be stimulated with continuous Gp 130 and STAT-3 activation in SOCS3-deficient macrophages 51 .…”
Section: Discussionmentioning
confidence: 99%
“…In Gp 130 Y757F mutant macrophages, the induction of transcriptional repressor can inhibit inflammatory gene responses in STAT-3 signaling by IL-6 50 . Therefore, efficient anti-inflammatory feedback can be stimulated with continuous Gp 130 and STAT-3 activation in SOCS3-deficient macrophages 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Raddeanin A is an attenuator of STAT3 signaling that has been investigated in many cancers as a potential drug for reversal of chemotherapy resistance [ 184 , 185 ]. Many additional agents that act by directly or indirectly reducing STAT3 signaling have been and are currently being investigated, some of which are FDA approved [ 186 , 187 , 188 ].…”
Section: Lif Signaling and Potential Therapeuticsmentioning
confidence: 99%
“…For example, danvatirsen, also known as AZD9150 or ISIS 481464, has been shown to reduce STAT3 mRNA and protein levels and block cell proliferation. Additionally, although danvatirsen is unsuitable for systemic administration because of its rapid degradation, similar to other siRNAs and decoy ODNs [55], the agent diminished the STAT3 protein level, thereby inhibiting the growth of subcutaneous xenograft tumors derived from human hepatocellular carcinoma and diffuse large B-cell lymphoma via intradermal and intratumoral injections, respectively [53, 54,56], and it was well tolerated at doses up to 30 mg/kg/week for 6 weeks in monkeys [57]. Critically, tumor biopsy samples from danvatirsen-treated patients have shown that its uptake was observed mainly in cells of the TME (but not cancer cells), suggesting that the clinical benefit was not due to direct tumor cell modulation, but rather through remodeling of the suppressive TME [58].…”
Section: Inhibitors Targeting the Dna-binding Domain (Dbd)mentioning
confidence: 99%
“…Taken together, the aforementioned evidence indicates that although encouraging data were obtained from preclinical studies, the use of OPB compounds as specific STAT3 inhibitors might be limited because of their effects on many signal transduction pathways. Additionally, there have been concerns about the potentially severe toxicities of OPB-51602 and OPB-31121, including susceptibility to opportunistic infections, which may limit their further development [74], reviewed in [55]. However, given the favorable safety profiles of OPB-111077, its combination with other treatment strategies might open a new avenue for future cancer therapy.…”
Section: Inhibitors Targeting the Dna-binding Domain (Dbd)mentioning
confidence: 99%
See 1 more Smart Citation